Improving the efficiency of the automated process of drying flotation concentrate in a drum drying furnace - Kovalev Igor; Kulmurodova Nafisa; Kulmurodov Zarifjon; Voroshilova Anna; Kadirov Yorkin; Ibodullaeva Dinara (E3S Web of Conferences)
The article analyzes the process of drying flotation concentrate in a drum drying furnace and considers a number of aspects of improving the efficiency of this technology. The study focuses on three main areas of optimization: managing humidity conditions, increasing energy efficiency and increasing the service life of equipment. The importance of maintaining optimal humidity of the flotation concentrate to ensure high product quality and efficient extraction of valuable components is emphasized. Modern technologies and systems for automatic humidity monitoring are considered. Methods for improving the energy efficiency of the process are discussed, including the introduction of heat recovery systems, the use of hybrid heating technologies and improved thermal insulation of equipment. Particular attention is paid to the automation of process control using specialized algorithms and machine learning. Issues of increasing the service life of equipment are considered. It is concluded that the implementation of the proposed measures to optimize the flotation concentrate drying process can ensure increased production efficiency, reduced operating costs and improved quality of the final product in the mining and metallurgical industry.